A kitchen and its furnishings - Tulloss, Elsie May (My University, 1908)
Introduction: A kitchen is that portion of a dwelling to which the preparation of pure, wholesome food is confined for the nourishment of our bodies. When it is realized how necessary it is that food be pure and wholesome and properly prepared, the first thing to look to, is a suitable place for its preparation.
Citation: Tulloss, Elsie May. A kitchen and its furnishings. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Domestic Science; Home Economics; Kitchens; Design; Graduating theses; Senior theses; Theses